The impact of academic leagues on student training: Recognition of the importance and benefits for the academic community (Research, Society and Development, 2024)
Academic Leagues (L.A.) are groups of students who seek to deepen their knowledge on specific topics, meeting the needs of the community, under the guidance of a teacher chosen by the students. Non-profit, these leagues promote teaching, research and extension. The Academic League of Orofacial Anatomy (LAAO) was created to integrate anatomy with orofacial harmonization (HOF) and forensic dentistry, areas little explored in undergraduate studies. This study seeks to identify whether L.A. contributes positively to the academic and personal training of students and benefits the entire academic community. Exploratory research was carried out, with quantitative and qualitative approaches. The non-probabilistic sample was composed of volunteer students, internal members of LAAO, from the 2nd to 12th semester of the Dentistry course, except those involved in the preparation of this article. Data collection took place through a questionnaire administered via "Google Forms". The analysis of the results highlights the importance of academic leagues in complementing training, promoting integration between theory and practice. They offer benefits to both students and the academic community, in addition to deepening essential knowledge for health courses and promoting a differentiated curriculum. The study confirms that Academic Leagues are fundamental for the training of undergraduates, providing significant benefits for academic and personal development. Students recognize their value and positive impact on the academic community, enhancing learning and encouraging integration.